Pengaruh Current Ratio dan Debt To Equity Ratio terhadap Kinerja Keuangan dengan Kebijakan Dividen Sebagai Variabel Moderating pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Riza Isnaini Adinda; Heny Triastuti Kurnia Ningsih; Jalilah Ilmiha (Universitas Islam Islam Sumatera Utara, 2026)
This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on financial performance proxied by Return on Assets (ROA), with dividend policy measured by Dividend Payout Ratio (DPR) as a Moderating variable in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2021–2025 period. This study is motivated by differences in the liquidity, capital structure, and profitability conditions of companies, which indicate inconsistent relationships based on previous studies. This research uses a quantitative approach with an associative research type. The population consists of 28 companies, and through purposive sampling, 17 companies were selected as research samples with a total of 85 observations. The data used are secondary data in the form of audited annual financial statements. The data analysis technique employed is Moderated Regression Analysis (MRA). The results of this study are expected to show that Current Ratio has a positive effect on Return on Assets, while Debt to Equity Ratio has a negative effect on Return on Assets. In addition, dividend policy is expected to strengthen the effect of Current Ratio on financial performance and weaken the negative effect of Debt to Equity Ratio on financial performance. This study is expected to contribute to the development of financial management knowledge and serve as a consideration for companies and investors in making financial decisions.